About the new version of maximum principle of Navier-Stokes equations - Akysh, A.Sh. (KSU publ., 2015)
The below shows the links of the extreme values of the velocity vector, the kinetic energy density and pressure of nonlinear Navier-Stokes equations. The latter shows the validity of the maximum principle for nonlinear Navier-Stokes equations that from a mathematical perspective is fundamentally-key.
Навье-Стокс теңдеулері үшін максимум қағидасының жаңа түрі туралы
О новом варианте принципа максимума для уравнений Навье-Стокса
Keywords: nonlinear Navier-Stokes equations system; the principle of maximum for Navier-Stokes equations; uniqueness of weak generalized solutions of Navier-Stokes equations; existence of strong solutions of Navier-Stokes equations